Practice and Experience in Advanced Research Computing 2021
DOI: 10.1145/3437359.3465578
|View full text |Cite
|
Sign up to set email alerts
|

Ookami: Deployment and Initial Experiences

Abstract: Ookami [3] is a computer technology testbed supported by the United States National Science Foundation. It provides researchers with access to the A64FX processor developed by Fujitsu [17] in collaboration with RIKΞN [35, 37] for the Japanese path to exascale computing, as deployed in Fugaku [36], the fastest computer in the world [34]. By focusing on crucial architectural details, the ARMbased, multi-core, 512-bit SIMD-vector processor with ultrahighbandwidth memory promises to retain familiar and successfu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Early study of the performance of FLASH on Ookami may be found in [8], and similar experiences are reported in [4,7]. The unoptimized performance on A64FX did not compare well to that found on traditional X86 architectures [5].…”
Section: Thermonuclear Supernovae With Flashmentioning
confidence: 73%
See 1 more Smart Citation
“…Early study of the performance of FLASH on Ookami may be found in [8], and similar experiences are reported in [4,7]. The unoptimized performance on A64FX did not compare well to that found on traditional X86 architectures [5].…”
Section: Thermonuclear Supernovae With Flashmentioning
confidence: 73%
“…The nodes have 32 GB of high-bandwidth memory, where 5 GB are reserved for the OS, leaving 27 GB for the user. These processors use the ARMv8.2-A Scalable Vector Extension (SVE) SIMD instruction set with a 512 bit vector implementation, allowing for vector lengths anywhere from 128-2048 bits and enabling vector length agnostic programming [5].…”
Section: Introduction 1ookami and A64fxmentioning
confidence: 99%
“…Mutations were introduced into wild-type (WT) models with MOE and PyMOL (PyMOL molecular graphics system). All MD simulations were conducted using the 2021 version of Gromacs software packages with the GROMOS96 53a6 force field. The protonation states of the amino acid residues under physiological conditions were determined using the H++ server .…”
Section: Methodsmentioning
confidence: 99%
“…As it was one of the marquee applications for the Ookami project, FLASH was ported as soon as Ookami was up and available. Sorting out the compilers and their options, versions of MPI, and requisite packages like the HDF5 library took some effort, but our initial experience with FLASH and other applications was overwhelmingly positive [3]. FLASH ran "right out of the box" with several compilers and MPI implementations, scaling reasonably well with no tuning.…”
Section: V2dmentioning
confidence: 99%
“…The project is run by Stony Brook University (SBU) in cooperation with the University at Buffalo [2] and provides open access along with training and resources to effectively use such hardware. Users have been able to port, analyze, and optimize the performance of many applications [3]. Below, we describe the hardware, our user base and education program, and provide highlights from previous performance studies of two astrophysical simulation codes, the astrophysical radiation hydrodynamics code V2D [4] and multi-application package FLASH [5,6], here applied to thermonuclear supernovae.…”
Section: Introductionmentioning
confidence: 99%